Using a Psychopharmacogenetic Approach To Identify the Pathways Through Which—and the People for Whom—Testosterone Promotes Aggression. (April 2019) - Geniole, Shawn N.; Procyshyn, Tanya L.; Marley, Nicole; Ortiz, Triana L.; Bird, Brian M.; Marcellus, Ashley L.; Welker, Keith M.; Bonin, Pierre L.; Goldfarb, Bernard; Watson, Neil V.; Carré, Justin M.
Little is known about the neurobiological pathways through which testosterone promotes aggression or about the people in whom this effect is observed. Using a psychopharmacogenetic approach, we found that testosterone increases aggression in men ( N = 308) with select personality profiles and that these effects are further enhanced among those with fewer cytosine-adenine-guanine (CAG) repeats in exon 1 of the androgen receptor (AR) gene, a polymorphism associated with increased AR efficiency. Testosterone's effects were rapid (~30 min after administration) and mediated, in part, by subjective reward associated with aggression. Testosterone thus appears to promote human aggression through an AR-related mechanism and to have stronger effects in men with the select personality profiles because it more strongly upregulates the subjective pleasure they derive from aggression. Given other evidence that testosterone regulates reward through dopaminergic pathways, and that the sensitivity of such pathways is enhanced among individuals with the personality profiles we identified, our findings may also implicate dopaminergic processes in testosterone's heterogeneous effects on aggression.